2016
DOI: 10.1007/s40520-016-0584-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte count ratio is associated with perforated appendicitis in elderly patients of emergency department

Abstract: We suggest that the initial NLR in the elderly patient is the most powerful predictive factor for the diagnosis of AA perforation in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
5
24
0
5
Order By: Relevance
“…AUC value of NLR was 0.755 (95% CI, 0.660-0.834), cut-off value was 5.6, sensitivity was 78.0%, and specificity was 65.9%. [16] In the current study, NLR value in group with appendicitis was statistically significantly higher than in control group, which was in accordance with results seen in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…AUC value of NLR was 0.755 (95% CI, 0.660-0.834), cut-off value was 5.6, sensitivity was 78.0%, and specificity was 65.9%. [16] In the current study, NLR value in group with appendicitis was statistically significantly higher than in control group, which was in accordance with results seen in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the ratio of these 2 subgroups (NLR) is used as a parameter of inflammation. [7][8][9][10][11][12][13] In a study designed by Kahramanca et al [9] it was determined that NLR was a useful parameter for diagnosing AA and discriminating between SA and CA. In a study involving 3392 cases, Sevinç et al [12] found that the WBC count was not a significant parameter in CA diagnosis, though it was significant in diagnosing AA.…”
Section: Discussionmentioning
confidence: 99%
“…The complete blood count (CBC) is one of the most commonly used laboratory tests for the diagnosis of AA. Many studies have focused on the role of white blood cell (WBC), neutrophil-to-lymphocyte ratio (NLR), platelet distribution width (PDW), mean platelet volume (MPV), red cell distribution width (RDW), platelet count (PLT), lymphocyte (L), neutrophil (N), C-reactive protein (CRP), and Lymphocyte-C-reactive protein ratio (LCR) values in the diagnosis of AA [4,8,[16][17][18]. We aimed to investigate the diagnostic efficacy of CBC parameters, CRP, and LCR in AA diagnosis and their relationship with appendix diameter.…”
Section: Introductionmentioning
confidence: 99%